2020
DOI: 10.1177/1758835920905424
|View full text |Cite
|
Sign up to set email alerts
|

An open label, multicenter, noninterventional study of apatinib in advanced gastric cancer patients (AHEAD-G202)

Abstract: Background: Apatinib has been proved to be effective and well tolerated among patients in phase II and III studies. Here, we evaluated the safety and effectiveness of apatinib in advanced gastric cancer patients in a real-world setting. Methods: This study enrolled advanced gastric cancer patients who had progressed or relapsed despite systemic chemotherapy. The primary outcome was safety and the secondary outcomes included overall survival (OS) and progression-free survival (PFS). Results: A total of 337 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…However, these doubts have not affected the large-scale clinical use of apatinib in patients with advanced GC in China. Subsequent clinical trial results revealed that apatinib showed acceptable efficacy and safety in real-world Chinese patients with metastatic GC (7,8); low doses of apatinib (250 mg or 500 mg/day) were tolerated by and beneficial to patients with advanced GC who had been heavily treated previously (9), and a lower dose of apatinib achieved comparable OS and PFS with a higher daily dose of apatinib while maintaining better safety (20). Apatinib has been further tested in other therapeutic scenarios.…”
Section: Gcmentioning
confidence: 99%
“…However, these doubts have not affected the large-scale clinical use of apatinib in patients with advanced GC in China. Subsequent clinical trial results revealed that apatinib showed acceptable efficacy and safety in real-world Chinese patients with metastatic GC (7,8); low doses of apatinib (250 mg or 500 mg/day) were tolerated by and beneficial to patients with advanced GC who had been heavily treated previously (9), and a lower dose of apatinib achieved comparable OS and PFS with a higher daily dose of apatinib while maintaining better safety (20). Apatinib has been further tested in other therapeutic scenarios.…”
Section: Gcmentioning
confidence: 99%
“… 4 Lower daily doses of apatinib have greater benefits than higher daily doses in advanced gastric cancer patients. 8 Apatinib also has reliable efficacy in advanced non‐small‐cell lung cancer (NSCLC) patients and chemotherapy‐refractory metastatic colorectal cancer. 6 , 9 Furthermore, apatinib enhances antitumour effect of chemotherapeutic drugs on several cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Apatinib prolongs median overall survival (mOS) and progression‐free survival (mPFS) of patients with advanced gastric cancer 4 . Lower daily doses of apatinib have greater benefits than higher daily doses in advanced gastric cancer patients 8 . Apatinib also has reliable efficacy in advanced non‐small‐cell lung cancer (NSCLC) patients and chemotherapy‐refractory metastatic colorectal cancer 6,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a real-world study of apatinib in advanced GC patients in China (AHEAD-G202) with 337 patients included showed that majority (95.6%) of patients received the dose of 250–500 mg and only 15 (4.4%) patients took 675–850 mg as the starting dose. 27 Moreover, the sub-analysis of the AHEAD-G202 study revealed no significant difference in PFS and OS among the low- (250 mg), mid- (425–500 mg), and high-dose (625–850 mg) groups. 28 In our study, the initial dosage of apatinib was 250 mg or 500 mg once daily at the discretion of the investigators.…”
Section: Discussionmentioning
confidence: 95%